Boron Incorporation by Hydrothermal Synthesis Into SAPO-5 and SAPO-11 Molecular Sieves - Rosângela Pedrosa Carvalho; Elisa Gabriela Costa Gouveia; Julyane da Rocha Santos Solano; Luciene Santos de Carvalho; Soraya Lira Alencar; Maritza Montoya Urbina; Antonio Osimar Sousa da Silva (Materials Research, 2022)
Abstract Silicoaluminophosphates SAPO-5 and SAPO-11 were synthesized using the hydrothermal method, 170 ºC with triethylamine and dipropylamine as the structure directing agents, respectively. This work aimed the incorporation of boron into the structures obtained by modifying the composition of the system, using as a reaction equation: Al2O3:P2O5:x SiO2: yB2O3:1,5TEA (or DPA):50H2O, with x, y=0-0.2. The phase was identified by XRD and characterized by FTIR, TGA/DTG, TPD-NH3 and nitrogen adsorption at -196°C. The structure parameters confirmed the obtaining of pure structures, showing a slight contraction in the parameters of the unit cells, indicating the presence of boron in the crystal lattice. The Brønsted sites, were modified up to a maximum of boron (y = 0.1) and for higher content, the acidity was not significant. The modification of weak acidity related to the appearance of isolated BO3 groups, indicating that the silicon atoms were not sufficiently distributed for the formation of sites.